OPTIMIZING ENGLISH WRITING WITH AI: UNLOCK THE POWER OF QUILLBOT - Safrida, Galuh; Puspitasari, Desi (Universitas Al-Qolam Malang, 2024)
AbstractThis research aims to determine the role of QuillBot as one of Artificial Intelligence (AI) in enhancing students’ writing skills. Artificial Intelligence (AI) is an advanced technology that can make a person's work easier. AI has a significant impact in various fields, such as education. Therefore, AI technology can assist students in completing their assignments. One such application is QuillBot, which aids students in improving their English writing. This research employed qualitative research using a questionnaire distributed via Google Forms. The findings indicate that Quillbot is beneficial for the students. It improves their paraphrasing skills, grammar, and vocabulary. This article is essential because readers can learn about the usefulness of AI applications, especially QuillBot, in writing English. It is also hoped that this research can encourage the adoption of similar technologies to support the learning process in various fields. Keywords: English Writing, AI, Paraphrasing tool, QuillBot